CRISPR-Cas9-mediated disruption of B2M and CIITA genes eliminates HLA class I and II expression in human induced pluripotent stem cells (MUSIi001-A-2) - Nontaphat Thongsin; Siriwal Suwanpitak; Methichit Wattanapanitch (Stem Cell Research, 2023)
Cell-based therapy offers great promise for treating degenerative diseases. Although autologous cell-based therapy is ideal, it may be impractical due to the high manufacturing cost and long production time. Allogeneic cell-based therapy offers a more cost-effective alternative; however, the risk of graft rejection is a major concern. Here, we generated HLA class-I and -II null iPSC line by knocking out CIITA gene in the B2M-knockout MUSIi001-A-1 cell line using CRISPR/Cas9 system. The MUSIi001-A-2 line provides a valuable model for studying immunological responses against allogeneic T cells and serves as a prototype for developing specific cell types for future cell-based therapy.